2022
DOI: 10.1186/s12884-022-04586-2
|View full text |Cite
|
Sign up to set email alerts
|

Mixed effect analysis of factors influencing the use of insecticides treated bed nets among pregnant women in Ghana: evidence from the 2019 Malaria Indicator Survey

Abstract: Background Malaria during pregnancy is a major cause of maternal morbidity globally and leads to poor birth outcomes. The World Health Organization has recommended the use of insecticide treated bed nets (ITN) as one of the effective malaria preventive strategies among pregnant women in malaria endemic areas. This study, therefore, seeks to examine the individual and household factors associated with the use of ITNs among pregnant women in Ghana. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
1
7
1
Order By: Relevance
“…This figures are greater than the prevalence recorded in sub-Saharan Africa (30.6%) and Madagascar (10.1%) [17]. The results, however, corroborate an earlier study conducted in Ghana [19] which reported a prevalence of 49.2%. Probably, the increase in the utilization of ITNs between 2011 and 2017 could be attributed to the implementation of the National Malaria Control Programme (NMCP), which provides free mass and continuous distribution of ITNs in hospitals and schools [20,21].…”
Section: Discussionsupporting
confidence: 83%
“…This figures are greater than the prevalence recorded in sub-Saharan Africa (30.6%) and Madagascar (10.1%) [17]. The results, however, corroborate an earlier study conducted in Ghana [19] which reported a prevalence of 49.2%. Probably, the increase in the utilization of ITNs between 2011 and 2017 could be attributed to the implementation of the National Malaria Control Programme (NMCP), which provides free mass and continuous distribution of ITNs in hospitals and schools [20,21].…”
Section: Discussionsupporting
confidence: 83%
“…However, other studies have reported older 58,59 or younger-aged pregnant women 20,60 slept more under ITNs. Though higher levels of education are associated with ITN use in pregnant women, 28,31 no such association was observed in the current study.…”
Section: Discussioncontrasting
confidence: 76%
“…22 Several studies have reported 32%-80.7% uptake of ⩾3 doses of IPTp-SP. [23][24][25][26][27] and ITN utilization of 40%-95% in pregnant women 25,[28][29][30][31] in Ghana over the last decade. However, there is a paucity of data on the uptake of these interventions and a limited understanding of local factors influencing them in the Ho Municipality of the Volta Region.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was higher than a study in Cameron (12.4%) [ 27 ], Uganda (35%) [ 28 ], Ghana 2019 malaria indicator survey (49.2%) [ 29 ], and Nigeria (43.3%) [ 30 ], and lower than the studies reported from Kenya (70.5%) [ 31 ], Multi-level analysis from SSA (74.2%) [ 32 ], and the Democratic Republic of Congo (76.4%) [ 33 ]. This could be due to differences in sociodemographic characteristics, norms, beliefs and other cultural variations across the study settings.…”
Section: Discussionmentioning
confidence: 69%